Flame-retardant styrene-based resin composition and molded article

JP7668701B2Active Publication Date: 2025-04-25PS JAPAN CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2021126214
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-30
Publication Date
2025-04-25
Estimated Expiration
2041-07-30

AI Technical Summary

Technical Problem

Existing flame-retardant styrene-based resin compositions face issues with poor dispersibility of flame retardants, generation of black smoke during combustion, and difficulty in achieving both low smoke emission and high rigidity while maintaining color tone and compatibility with bromine-free and bio-based materials.

Method used

A styrene resin composition comprising 60-96.7% styrene resin, 3-30% phosphinate compound, and 0.3-10% cellulose-based polysaccharide, specifically selected for their flame-retardant properties and compatibility, ensuring low smoke emission, flame retardancy, and excellent color tone.

Benefits of technology

The composition achieves low smoke emission, high flame retardancy, and excellent rigidity with improved color tone, meeting environmental and material compatibility requirements.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a flame-retardant styrenic resin composition that has reduced environmental load and is excellent in terms of low smoke emission, flame retardancy, rigidity and color tone.SOLUTION: A flame-retardant styrenic resin composition contains a styrenic resin (A) 60-96.7 mass%, a flame retardant (B) containing phosphinate (b) 3-30 mass%, and a cellulosic polysaccharide with an average length of a minor axis d1 and / or a major axis d2 being less than 0.1-10 μm (C) 0.3-10 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to flame-retardant styrene-based resin compositions and molded articles. [Background technology]

[0002] Styrene resins are used in a wide range of applications due to their excellent moldability, dimensional stability, and impact resistance. In particular, flame-retardant polystyrene resin compositions are used in a wide variety of products, including home appliances and office automation equipment, and there is currently a demand for thinner products due to reduction or weight reduction. Conventionally, various flame retardants have been proposed to impart flame retardancy to polystyrene resin compositions. Among these, bromine-based flame retardants, which are inexpensive and have an excellent balance of physical properties, are widely used. However, in recent years, due to the increasing movement to regulate halogen-containing organic compounds, particularly in Europe, there is a growing demand for flame-retardant resins or flame-retardant resin compositions that do not contain bromine. Furthermore, from a carbon neutrality perspective, there is a growing need for materials containing bio-based components.

[0003] As an alternative flame retardant to these bromine-based flame retardants, for example, Patent Document 1 discloses a technique of adding a phosphinate to a thermoplastic polymer. Furthermore, Patent Document 2 discloses a technique for improving flame retardancy by adding a flame retardant and cellulose nanofibers to a thermoplastic resin. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-124466 [Patent Document 2] International Publication No. 2017 / 169494 brochure [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] Although Patent Document 1, mentioned above, describes a method for imparting flame retardancy to polystyrene resin compositions, the flame retardant described in Patent Document 1 has poor dispersibility in polystyrene, resulting in insufficient flame retardancy and problems such as the generation of black smoke during combustion. Furthermore, while the technology described in Patent Document 2 improves flame retardancy by incorporating the specified flame retardant and cellulose nanofibers described in Patent Document 2 into the polystyrene resin composition, it fails to prevent black smoke during the combustion of polystyrene and does not consider achieving both low smoke emission and high rigidity. Moreover, when processing the polystyrene resin composition, it turns brown, making it difficult to color it white, which is another problem.

[0006] Therefore, the present invention aims to provide a flame-retardant styrene-based resin composition that reduces environmental impact, combines low smoke emission and flame retardancy, and exhibits excellent rigidity and color tone. [Means for solving the problem]

[0007] As a result of diligent research to solve the above problems, the inventors of the present invention have discovered, to their surprise, that a resin composition obtained by adding a phosphinate compound (b) and a specific cellulosic polysaccharide (C) to styrene resin in specific proportions exhibits extremely high flame retardancy, low smoke emission, rigidity, and excellent color tone, thus completing the present invention. In other words, the present invention is as follows.

[0008] [1] The present invention comprises 60 to 96.7% by mass of styrene resin (A), The following general formula (i): [ka] [In the above equation (i), R i1 and R i2 Each of these is independently either unsubstituted or has one or more hydrogen atoms substituted R i3 A linear or branched alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an aralkyl group having 6 to 14 carbon atoms, which may be substituted by: The substituent R i3is the following formula (ii):

Chemical formula

Chemical formula

[0009] The present invention aims to provide a flame-retardant styrene-based resin composition that reduces environmental impact, combines low smoke emission and flame retardancy, and exhibits excellent rigidity and color tone. [Modes for carrying out the invention]

[0010] The embodiments of the present invention (hereinafter referred to as "this embodiment") will be described in detail below, but the present invention is not limited to the following description and can be implemented in various ways within the scope of its gist.

[0011] [Flame-retardant styrene resin composition] The flame-retardant styrene resin composition of this embodiment contains 60 to 96.7% by mass of styrene resin (A) (hereinafter also referred to as component (A)), 5 to 30% by mass of flame retardant (B) (hereinafter also referred to as component (B)) consisting of a phosphinate compound (b), and 0.3 to 10% by mass of cellulose polysaccharide (C) (hereinafter also referred to as component (C)) having an average length of at least one of the short axis d1 or long axis d2 of less than 0.1 to 10 μm. The phosphinate compound (b) is the following general formula (i): [ka] [In the above equation (i), R i1 and R i2 Each of these is independently either unsubstituted or has one or more hydrogen atoms substituted R i3 A linear or branched alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an aralkyl group having 6 to 14 carbon atoms, which may be substituted by: The substituent R i3 This is expressed by the following formula (ii): [ka] In the above formula (ii), R ii1Each of these is independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, and * represents a bond with another atom. M i is at least one selected from the group consisting of calcium ions, magnesium ions, aluminum ions, zinc ions, bismuth ions, manganese ions, sodium ions, potassium ions, and protonated nitrogen bases, p + is M i It represents the ion valency, and is a positive integer from 1 to 3, m i1 n is a positive integer between 1 and 3. - |p| represents a negative integer of -1, -2, or -3. + ×r|=|n - xm i1 It is represented by ]. This makes it possible to provide a flame-retardant styrene-based resin composition with excellent low smoke emission, flame retardancy, rigidity, and color tone. The following describes each component contained in the flame-retardant styrene resin composition.

[0012] <Styrene resin (A): Component (A)> In the flame-retardant styrene-based resin composition of this embodiment, the content of styrene-based resin (A) is 60 to 96.7% by mass, preferably 65 to 95% by mass, and more preferably 60 to 90% by mass, based on 100% by mass of the total amount of components (A), (B), and (C). If the content of styrene-based resin (A) is less than 60% by mass, the moldability decreases, and if it exceeds 96.7% by mass, the flame retardancy decreases.

[0013] The styrene-based resin (A) that can be used in this embodiment is preferably a resin obtained by polymerizing a styrene-based monomer with one or more vinyl-based monomers and rubbery polymers (a) selected as needed, which can copolymerize with the styrene-based monomer. In other words, the styrene-based resin (A) is preferably a polymer having styrene-based monomer units, and more preferably a polymer that essentially contains styrene-based monomer units and optionally contains monomer units of other vinyl-based monomers and / or rubbery polymers (a) copolymerizable with the styrene-based monomer units. The preferred form of the styrene-based resin (A) in this embodiment is not particularly limited, but specifically, examples include a rubber-modified styrene-based resin in which particles of the rubbery polymer (a) are dispersed in a polymer matrix containing polystyrene, a polystyrene-based polymer (such as a polystyrene and / or polystyrene-unsaturated carboxylic acid polymer), or a styrene-based copolymer resin. Furthermore, a styrene-based polymer having a syndiotactic structure can also be used as the styrene-based resin (A).

[0014] <Polystyrene> In this embodiment, polystyrene is a homopolymer obtained by polymerizing styrene monomers, and commonly available ones can be appropriately selected and used. Examples of styrene monomers constituting polystyrene include, in addition to styrene, α-methylstyrene, α-methyl-p-methylstyrene, ο-methylstyrene, m-methylstyrene, p-methylstyrene, vinyltoluene, ethylstyrene, isobutylstyrene, and styrene derivatives such as t-butylstyrene or bromostyrene and indene. Styrene is particularly preferred from an industrial standpoint. One or more of these styrene monomers can be used. Polystyrene may further contain monomer units other than the above-mentioned styrene monomer units, as long as it does not impair the effects of the present invention, but it typically consists of styrene monomer units.

[0015] <<Rubber-modified styrene resin>> In this embodiment, the rubber-modified styrene resin is a styrene resin matrix in which particles of rubbery polymer (a) (also referred to as rubbery polymer (a) particles) are dispersed, and can be produced by polymerizing a styrene monomer in the presence of rubbery polymer (a).

[0016] In addition to styrene, the styrene monomers constituting the rubber-modified styrene resin of this embodiment include, for example, α-methylstyrene, α-methylp-methylstyrene, ο-methylstyrene, m-methylstyrene, p-methylstyrene, vinyltoluene, ethylstyrene, isobutylstyrene, and styrene derivatives such as t-butylstyrene or bromostyrene and indene. Styrene is particularly preferred. One or more of these styrene monomers can be used.

[0017] The rubber-like polymer (a) particles contained in the rubber-modified styrene resin of this embodiment may, for example, contain a resin containing styrene monomer units obtained from the above-mentioned styrene monomer inside the rubber-like polymer (a) particles, and / or have a resin containing styrene monomer units grafted onto the surface of the rubber-like polymer (a) particles.

[0018] As the rubbery polymer (a), for example, rubber components such as polybutadiene, polyisoprene, natural rubber, polychloroprene, styrene-butadiene copolymer, and acrylonitrile-butadiene copolymer can be used. Furthermore, the rubber component may also contain polystyrene and / or polystyrene-unsaturated carboxylic acid polymers. Among these, polybutadiene or styrene-butadiene copolymer is preferred as the rubbery polymer (a). Both high-cis polybutadiene with a high cis content and low-cis polybutadiene with a low cis content can be used for the polybutadiene. Furthermore, both random and block structures can be used for the styrene-butadiene copolymer. One or more of these rubbery polymers (a) can be used. Saturated rubber obtained by hydrogenating butadiene-based rubber can also be used.

[0019] Examples of such rubber-modified styrene resins include HIPS (high-impact polystyrene), ABS resin (acrylonitrile-butadiene-styrene copolymer), AAS resin (acrylonitrile-acrylic rubber-styrene copolymer), and AES resin (acrylonitrile-ethylene propylene rubber-styrene copolymer).

[0020] When the rubber-modified styrene resin is a HIPS resin, among these rubbery polymers (a), high-cis polybutadiene composed of 90 mol% or more cis-1,4 bonds is particularly preferred. In the high-cis polybutadiene, it is preferable that vinyl-1,2 bonds be composed of 6 mol% or less, and particularly preferable that they be composed of 3 mol% or less. Furthermore, the content of isomers of the constituent units of the above-mentioned isis-polybutadiene that have a cis-1,4 structure, a trans-1,4 structure, or a vinyl-1,2 structure can be calculated by measuring with an infrared spectrophotometer and processing the data using the Morello method. Furthermore, the above-mentioned high-cis polybutadiene can be easily obtained by polymerizing 1,3-butadiene using a known production method, for example, a catalyst containing an organoaluminum compound and a cobalt or nickel compound.

[0021] The content of the rubber-like polymer (a) contained in the rubber-modified styrene resin (excluding the styrene resin as a matrix incorporated into the rubber-like polymer (a) particles) is preferably 3 to 20% by mass, and more preferably 5 to 15% by mass, based on 100% by mass of the total amount of the rubber-modified styrene resin. If the content of the rubber-like polymer (a) is less than 3% by mass, the impact resistance of the styrene resin may decrease. Also, if the content of the rubber-like polymer (a) exceeds 20% by mass, the flame retardancy may decrease.

[0022] In this disclosure, the content of the rubbery polymer (a) contained in the rubber-modified styrene resin is a value calculated using pyrolysis gas chromatography.

[0023] The average particle size of the rubbery polymer (a) particles contained in the rubber-modified styrene resin is preferably 0.5 to 4.0 μm, and more preferably 0.8 to 3.5 μm, from the viewpoint of impact resistance and flame retardancy.

[0024] In this disclosure, the average particle size of the rubbery polymer (a) particles contained in the rubber-modified styrene resin can be measured by the following method. Ultrathin sections with a thickness of 75 nm were prepared from a rubber-modified styrene resin stained with osmium tetroxide, and photographs were taken at a magnification of 10,000x using an electron microscope. In the photograph, the black-stained particles are rubbery polymer (a) particles. From the photograph, the following formula (N1) is derived: Average particle size=ΣniDri 3 / ΣniDri 2 (N1) (In the above formula (N1), ni is the number of rubbery polymer (a) particles with particle size Dri, and particle size Dri is the particle size calculated as the equivalent circle diameter from the area of ​​the particles in the photograph.) The area-average particle diameter is calculated and used as the average particle diameter of the rubbery polymer (a) particles. This measurement is performed by scanning a photograph at a resolution of 200 dpi and measuring it using the particle analysis software of the image analysis device IP-1000 (manufactured by Asahi Kasei Corporation).

[0025] The reduced viscosity of the rubber-modified styrene resin (which is an indicator of the molecular weight of the rubber-modified styrene resin) is preferably in the range of 0.50 to 0.85 dL / g, and more preferably in the range of 0.55 to 0.80 dL / g. If it is less than 0.50 dL / g, the impact strength may decrease, and if it exceeds 0.85 dL / g, the moldability may decrease due to a decrease in fluidity.

[0026] In this disclosure, the reduced viscosity of the rubber-modified styrene resin is the value measured in a toluene solution at 30°C and a concentration of 0.5 g / dL.

[0027] The method for producing rubber-modified styrene resins is not particularly limited, but they can be produced by bulk polymerization (or solution polymerization) in which styrene monomers (and a solvent) are polymerized in the presence of a rubbery polymer (a), or by bulk-suspension polymerization in which the reaction transitions to suspension polymerization, or by emulsion graft polymerization in which styrene monomers are polymerized in the presence of a rubbery polymer (a) latex. In bulk polymerization, the resin can be produced by continuously supplying a mixed solution of the rubbery polymer (a), styrene monomers, and optionally an organic solvent, organic peroxide, and / or chain transfer agent to a polymerization apparatus configured by connecting a fully mixed reactor or a tank reactor and multiple tank reactors in series.

[0028] <<Styrene-based copolymer resin>> In this embodiment, the styrene copolymer resin is a resin containing styrene monomer units and other monomers copolymerizable with the styrene monomers (for example, unsaturated carboxylic acid monomer units). For example, when the other monomers are unsaturated carboxylic acid monomer units, the styrene copolymer resin according to the present invention preferably contains 69 to 98% by mass, more preferably 74 to 96% by mass, and even more preferably 77 to 92% by mass, when the total content of styrene monomer units and unsaturated carboxylic acid monomer units is 100% by mass. By setting the content to 69% by mass or more, the fluidity of the resin can be improved. On the other hand, by setting the content of styrene monomer units to 98% by mass or less, it becomes difficult to have a desired amount of unsaturated carboxylic acid monomer units, which are an example of other monomers, and it becomes difficult to obtain the effects of these monomer units described later.

[0029] In this embodiment, the unsaturated carboxylic acid monomer includes unsaturated carboxylic acid monomers and unsaturated carboxylic acid ester monomers.

[0030] In the preferred styrene copolymer resin of this embodiment, unsaturated carboxylic acid monomer units play a role in improving heat resistance. When the total content of styrene monomer units, unsaturated carboxylic acid monomer units, and unsaturated carboxylic acid ester monomer units in the styrene copolymer resin is 100% by mass, the content of unsaturated carboxylic acid monomer units is preferably 2 to 16% by mass, more preferably 4 to 14% by mass, and even more preferably 8 to 13% by mass. By setting the content to 2% by mass or more, the dispersibility of component (B) is improved and the heat resistance can be further improved. On the other hand, by setting the content to 16% by mass or less, when the flame-retardant styrene-based resin composition of this embodiment is used as a masterbatch, excellent dispersibility with respect to the styrene-based resin is exhibited, flame retardancy can be improved, and the molded appearance, resin fluidity, and mechanical properties can be further improved.

[0031] Generally, styrene-methacrylic acid-methyl methacrylate copolymer resins, which are one form of the styrene-based copolymer resin in the present invention, are almost always produced by radical polymerization on an industrial scale. However, in this embodiment, various alcohols can be added to the polymerization system to suppress the gelation reaction in the defoliation step.

[0032] Unsaturated carboxylic acid ester monomers can be used to suppress the dehydration reaction of unsaturated carboxylic acid monomers through intermolecular interactions and to improve the mechanical strength of resins. Furthermore, unsaturated carboxylic acid ester monomers also contribute to improving resin properties such as weather resistance and surface hardness.

[0033] In this embodiment, when the total content of styrene monomer units, unsaturated carboxylic acid monomer units, and unsaturated carboxylic acid ester monomer units is set to 100% by mass, the content of unsaturated carboxylic acid ester monomer units is preferably 0 to 15% by mass, more preferably 1 to 12% by mass, and even more preferably 2 to 10% by mass. By setting the content to 15% by mass or less, the fluidity of the resin can be improved and water absorption can be suppressed. Furthermore, by setting the lower limit of the content of unsaturated carboxylic acid ester monomer units to 0% by mass, heat resistance can be improved and costs can be reduced, but from the above viewpoint, the content of unsaturated carboxylic acid ester monomer units can also be greater than 0% by mass.

[0034] Furthermore, when an unsaturated carboxylic acid monomer and an unsaturated carboxylic acid ester monomer unit are bonded adjacent to each other, a de-alcoholization reaction may occur under certain conditions when a high-temperature, high-vacuum defloration apparatus is used, forming a six-membered cyclic acid anhydride. The styrene copolymer resin of this embodiment may contain this six-membered cyclic acid anhydride, but it is preferable to have as little of the generated six-membered cyclic acid anhydride as possible, as it reduces fluidity.

[0035] In this embodiment, the content of styrene monomer units (e.g., styrene monomer units), unsaturated carboxylic acid monomer units (e.g., methacrylic acid monomer units), and unsaturated carboxylic acid ester monomer units (e.g., methyl methacrylate monomer units) in the styrene copolymer resin is determined by proton nuclear magnetic resonance ( 1 It can be determined from the integral ratio of the spectrum measured with a 1H-NMR detector.

[0036] In this embodiment, the styrene copolymer resin may further contain monomer units other than styrene monomer units and, as an example of other monomers, unsaturated carboxylic acid monomers (e.g., unsaturated carboxylic acid monomer units and unsaturated carboxylic acid ester monomer units), to the extent that it does not impair the effects of the present invention. However, the styrene copolymer resin in the present invention is preferably typically composed of styrene monomer units, unsaturated carboxylic acid monomer units, and / or unsaturated carboxylic acid ester monomer units.

[0037] The styrene monomer constituting the styrene copolymer resin of this embodiment is not particularly limited, but examples include styrene, α-methylstyrene, α-methyl-p-methylstyrene, ο-methylstyrene, m-methylstyrene, p-methylstyrene, vinyltoluene, ethylstyrene, isobutylstyrene, t-butylstyrene, bromostyrene, indene, and other styrene derivatives. From an industrial standpoint, styrene is preferred as the styrene monomer. These styrene monomers can be used individually or in combination of two or more.

[0038] The unsaturated carboxylic acid monomers constituting the styrene copolymer resin of this embodiment are not particularly limited, but examples include methacrylic acid, acrylic acid, maleic anhydride, maleic acid, fumaric acid, itaconic acid, etc. Methacrylic acid is preferred as the unsaturated carboxylic acid monomer because it has a significant effect in improving heat resistance and is liquid at room temperature, making it easy to handle. These unsaturated carboxylic acid monomers can be used individually or in combination of two or more.

[0039] The unsaturated carboxylic acid ester monomers constituting the styrene copolymer resin of this embodiment are not particularly limited, but examples include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, and cyclohexyl (meth)acrylate. Methyl (meth)acrylate is preferred as the (meth)acrylate monomer because it has little effect on the reduction of heat resistance. These unsaturated carboxylic acid ester monomers can be used individually or in combination of two or more.

[0040] Suitable styrene-based copolymer resins for this embodiment include styrene-methacrylic acid copolymer, styrene-methyl methacrylate copolymer, styrene-methacrylic acid-methyl methacrylate copolymer, styrene-acrylic acid copolymer, styrene-methyl acrylate copolymer, styrene-acrylic acid-methyl acrylate copolymer, styrene-methyl methacrylate-butyl methacrylate copolymer, styrene-butyl methacrylate copolymer, or styrene-maleic anhydride copolymer.

[0041] In this embodiment, the weight-average molecular weight (Mw) of the styrene copolymer resin is preferably 100,000 to 350,000, more preferably 120,000 to 300,000, and even more preferably 140,000 to 240,000. When the weight-average molecular weight (Mw) is 100,000 to 350,000, a resin with a better balance of mechanical strength and fluidity is obtained, and the inclusion of gel material is also reduced. The weight-average molecular weight (Mw) is a value obtained using gel permeation chromatography on a standard polyethylene basis.

[0042] In this embodiment, there are no particular restrictions on the polymerization method of the styrene-based polymer resin, but for example, a bulk polymerization method or a solution polymerization method can be suitably employed as a radical polymerization method. The polymerization method mainly comprises a polymerization step of polymerizing the polymerization raw material (monomer component) and a defoliation step of removing volatile components such as unreacted monomers and polymerization solvents from the polymerization product.

[0043] The following describes an example of a polymerization method for styrene copolymer resins that can be used in this embodiment.

[0044] When polymerizing polymerization raw materials to obtain styrene copolymer resins, the polymerization raw material composition typically contains a polymerization initiator and a chain transfer agent.

[0045] Polymerization initiators used in the polymerization of styrene copolymer resins include organic peroxides, such as peroxyketals like 2,2-bis(t-butylperoxy)butane, 1,1-bis(t-butylperoxy)cyclohexane, and n-butyl-4,4-bis(t-butylperoxy)valerate; dialkyl peroxides like di-t-butylperoxide, t-butylcumylperoxide, and dicumylperoxide; diacyl peroxides like acetylperoxide and isobutyrylperoxide; peroxydicarbonates like diisopropylperoxydicarbonate; peroxyesters like t-butylperoxyacetate; ketone peroxides like acetylacetone peroxide; and hydroperoxides like t-butylhydroperoxide. Of these, 1,1-bis(t-butylperoxy)cyclohexane is preferred from the viewpoint of decomposition rate and polymerization rate.

[0046] Examples of chain transfer agents used in the polymerization of styrene copolymer resins include α-methylstyrene linear dimer, n-dodecyl mercaptan, t-dodecyl mercaptan, and n-octyl mercaptan.

[0047] As a polymerization method for styrene copolymer resins, solution polymerization using a polymerization solvent can be employed as needed. Examples of polymerization solvents that can be used include aromatic hydrocarbons, such as ethylbenzene and dialkyl ketones, such as methyl ethyl ketone. These may be used individually or in combination of two or more. Other polymerization solvents, such as aliphatic hydrocarbons, can be further mixed with aromatic hydrocarbons as long as they do not reduce the solubility of the polymerization product. It is preferable that these polymerization solvents are used in an amount not exceeding 25 parts by mass per 100 parts by mass of total monomers. If the amount of polymerization solvent exceeds 25 parts by mass per 100 parts by mass of total monomers, the polymerization rate tends to decrease significantly, and the mechanical strength of the resulting resin tends to decrease greatly. Adding 5 to 20 parts by mass per 100 parts by mass of total monomers before polymerization is preferable in terms of quality uniformity and polymerization temperature control.

[0048] In this embodiment, there are no particular restrictions on the apparatus used in the polymerization step to obtain the styrene copolymer resin, and it may be appropriately selected according to the polymerization method of the styrene copolymer resin. For example, when bulk polymerization is employed, one or more fully mixed reactors can be used in the polymerization apparatus. There are also no particular restrictions on the devolatilization step. When bulk polymerization is employed, polymerization is carried out until the amount of unreacted monomer is preferably 50% by mass or less, more preferably 40% by mass or less, and then devolatilization is performed by known methods to remove volatile components such as the unreacted monomer. More specifically, conventional devolatilization equipment such as flash drums, twin-screw devolatars, thin-film evaporators, and extruders can be used, but devolatilization equipment with fewer retention areas is preferred. The temperature for the devolatilization treatment is usually around 190 to 280°C, and 190 to 260°C is more preferred from the viewpoint of suppressing the formation of six-membered ring acid anhydrides due to the proximity of unsaturated carboxylic acid monomers (e.g., methacrylic acid) and unsaturated carboxylic acid ester monomers (e.g., methyl methacrylate). Furthermore, the pressure used for devolatilization is typically around 0.13 to 4.0 kPa, preferably 0.13 to 3.0 kPa, and more preferably 0.13 to 2.0 kPa. Desirable devolatilization methods include, for example, removing volatile components by reducing pressure under heating, and removing them by passing the material through an extruder or the like designed for the purpose of removing volatile components.

[0049] <Flame retardant (B): (B) component> The flame-retardant styrene resin composition of this embodiment contains 3 to 30% by mass of flame retardant (B) per 100% by mass of the flame-retardant styrene resin composition, preferably 5 to 29% by mass, more preferably 8 to 28% by mass, and even more preferably 10 to 25% by mass. Furthermore, in this embodiment, the content of phosphinate compound (b) is preferably 70% by mass or more based on 100% by mass of the total amount of flame retardant (B). Therefore, other known flame retardants and / or optional additives (antioxidants, UV inhibitors, etc.) described later may be included in amounts of 30% by mass or less based on 100% by mass of the total amount of flame retardant (B). In this embodiment, the phosphinate compound (b) is represented by the following general formula (i) and preferably contains at least one phosphinate selected from phosphinates and diphosphinates, and more preferably the phosphinates account for 70% by mass or more of the total phosphinate compound (b) (100% by mass). The following general formula (i): [ka] [In the above equation (i), R i1 and R i2 Each of these is independently either unsubstituted or has one or more hydrogen atoms substituted R i3 A linear or branched alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an aralkyl group having 6 to 14 carbon atoms, which may be substituted by: The substituent R i3 This is expressed by the following formula (ii): [ka] In the above formula (ii), R ii1 Each of these is independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, and * represents a bond with another atom. M i is at least one selected from the group consisting of calcium ions, magnesium ions, aluminum ions, zinc ions, bismuth ions, manganese ions, sodium ions, potassium ions, and protonated nitrogen bases, p + is M i It represents the ion valency, and is a positive integer from 1 to 3, m i1 n is a positive integer between 1 and 3. - |p| represents a negative integer of -1, -2, or -3, and r is a positive integer of 1 to 3. + ×r|=|n - xm i1 | is also R i1 and R ii1 If there are multiple instances of each, each R i1 and R ii1They may be the same or different. Therefore, the phosphinate compound (b) in this embodiment may contain a known flame retardant other than phosphinates represented by general formula (i) in an amount of 30% by mass or less relative to the total phosphinate compound (b) (100% by mass). In the above formula (i), M i The ion value of "p + The absolute value of the product of " and "r" is "n - " and "m i1 It is equal to the absolute value of the product of and . In (i) above, p + 1 or 2 is preferred. i1 1 or 2 is preferred. - For -1 or -2, r is preferably 1 or 2.

[0050] In this embodiment, preferred phosphinates are those represented by the following general formula (1). [ka] [In the above formula (1), R 11 and R 12 Each is independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms; M 1 is at least one selected from the group consisting of calcium ions, magnesium ions, aluminum ions, zinc ions, bismuth ions, manganese ions, sodium ions, potassium ions, and protonated nitrogen bases; a is M 1 This represents the ion valency, and is an integer between 1 and 3; m 1 a is an integer between 1 and 3; a = m 1 That is. R 11 and R 12 If there are multiple instances of each, each R 11 and R 12 They may be the same or different.

[0051] In this embodiment, preferred diphosphinate salts are those represented by the following general formula (2). [ka] [In the above equation (2), R 21 and R 22 Each is independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms; L 23 This is a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 6 to 14 carbon atoms, or an arylalkylene group having 6 to 14 carbon atoms; M 2 b is at least one selected from the group consisting of calcium ions, magnesium ions, aluminum ions, zinc ions, bismuth ions, manganese ions, sodium ions, potassium ions, and protonated nitrogen bases; b is M 2 This represents the ion valency, and is an integer between 1 and 3; m 2 b is an integer between 1 and 3; q is an integer of 1 or 2; b × q = 2m 2 That is. R 21 and R 12 If there are multiple instances of each, each R 21 and R 22 They may be the same or different. At least one is selected from the group consisting of ].

[0052] In the above formulas (i), (ii), (1), and (2), examples of linear or branched alkyl groups having 1 to 6 carbon atoms include linear alkyl groups such as methyl, ethyl, propyl, butyl, amyl, or hexyl groups, and branched alkyl groups such as isopropyl, isobutyl, s-butyl, t-butyl, isoamyl, or t-amyl groups. In the above formulas (i), (ii), (1), and (2), the aryl group having 6 to 10 carbon atoms may have a monocyclic or fused ring structure. Examples include the phenyl group or the naphthyl group. In the above formula (2), the linear or branched alkylene group having 1 to 10 carbon atoms is a group obtained by removing one hydrogen atom from the above linear or branched alkyl group having 1 to 6 carbon atoms. In the above formula (2), the arylene group having 6 to 10 carbon atoms is a group obtained by removing one hydrogen atom from the above aryl group having 6 to 10 carbon atoms. In the above formula (i), the aralkyl group having 6 to 14 carbon atoms includes a benzyl group, a phenylethyl group, a phenylpropyl group, a phenylbutyl group, a methylphenyl group, an ethylphenyl group, a propylphenyl group, a butylphenyl group, a methylnaphthyl group, an ethylnaphthyl group, or a tert-butylnaphthyl group. In the above formula (2), examples of the alkylarylene group having 6 to 14 carbon atoms include a methylphenylene group, an ethylphenylene group, a tert-butylphenylene group, a methylnaphthylene group, an ethylnaphthylene group, and a tert-butylnaphthylene group. In the above formula (2), examples of the arylalkylene group having 6 to 14 carbon atoms include a phenylmethylene group, a phenylethylene group, a phenylpropylene group, and a phenylbutylene group. In the above formula (1), R 11 and R 12 are each independently preferably a linear alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms. In the above formula (1), M 1 is preferably calcium, magnesium, aluminum, or zinc. Also, a+ represents the ionic valence of M 1 [[ID= / / ID=20]]and is 2 or 3. In the above formula (2), R 21 and R 22 are each independently preferably a linear alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms. In the above formula (2), L 23 is each independently preferably a linear alkylene group having 1 to 6 carbon atoms or an arylene group having 6 to 10 carbon atoms. In the above formula (2), M 2 Note: There seems to be a formatting issue in the original text where line ID=20 is cut off. I've translated it as best as possible with the available information. If there's a mistake in the original text's line ID=20, the translation might need adjustment accordingly.Calcium, magnesium, aluminum, or zinc are preferred. Also, b+ is M 2 This represents the ionic charge, which is 2 or 3. Phosphinate compound (b) has excellent electrical properties, making it suitable for flame-retardant materials where insulation is required. It also has excellent hydrolytic properties, making it suitable for use in high-temperature and high-humidity environments, and it is highly recyclable.

[0053] The phosphinate compound (b) used in this embodiment is, in particular, a monomeric compound produced in aqueous solution using phosphinic acid and a metal carbonate, metal hydroxide, or metal oxide. However, depending on the reaction conditions and environment, polymeric phosphinates with a degree of condensation of 1 to 3 may also be included.

[0054] Such phosphinate compounds (b) are not particularly limited, but include, for example, calcium dimethylphosphinate, magnesium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, magnesium ethylmethylphosphinate, aluminum ethylmethylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, magnesium diethylphosphinate, aluminum diethylphosphinate, zinc diethylphosphinate, calcium methyl-n-propylphosphinate, magnesium methyl-n-propylphosphinate, aluminum methyl-n-propylphosphinate, zinc methyl-n-propylphosphinate, calcium methanedi(methylphosphinate), magnesium methanedi(methylphosphinate), aluminum methanedi(methylphosphinate), zinc methanedi(methylphosphinate), calcium benzene-1,4-(dimethylphosphinate), and benzene-1 Examples include magnesium 4-(dimethylphosphinate), aluminum benzene-1,4-(dimethylphosphinate), zinc benzene-1,4-(dimethylphosphinate), calcium methylphenylphosphinate, magnesium methylphenylphosphinate, aluminum methylphenylphosphinate, zinc methylphenylphosphinate, calcium diphenylphosphinate, magnesium diphenylphosphinate, aluminum diphenylphosphinate, and zinc diphenylphosphinate. Preferably, it is calcium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, aluminum ethylmethylphosphinate, aluminum ethylbutylphosphinate, aluminum dibutylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, aluminum diethylphosphinate, and zinc diethylphosphinate, and more preferably, aluminum diethylphosphinate. Examples of commercially available phosphinate compounds (b) include, but are not limited to, Exolit® OP1230, OP1240, OP1311, OP1312, OP930, and OP935 manufactured by Clariant Japan.

[0055] In this embodiment, the phosphinate compound (b) is preferably granular. When the phosphinate compound (b) is granular, the average particle size of the phosphinate compound (b) is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 20 μm or less, from the viewpoint of improving the mechanical strength and appearance of the molded article obtained by molding the flame-retardant resin composition of this embodiment, and it is preferable to use a powder of the phosphinate compound (b) that has been ground to this particle size. Preferably, it is more than 0.5 μm and 20 μm, and more preferably more than 1 μm and 20 μm or less. Using a powder with a preferred particle size is particularly preferable because it not only exhibits high flame retardancy but also significantly increases impact strength. When the average length of the short axis d1 or long axis d2 of the cellulose polysaccharide (C) (e.g., cellulose nanofibers) is smaller than the average particle size of the phosphinate compound (b), the cellulose polysaccharide (C) (e.g., cellulose nanofibers) adheres to (or clings to) the phosphinate compound (b), thereby improving the dispersibility of each component in the flame-retardant resin composition (especially the cellulose polysaccharide (C) or the phosphinate compound (b)). This makes it possible to provide a flame-retardant styrene-based resin composition that combines low smoke emission and flame retardancy, and also has superior rigidity and color. On the other hand, in the case of cellulose fibers, which are larger than phosphinate compound (b), the flame retardant components such as phosphinate compound (b) adhere to (or cling to) the cellulose fibers. The average particle size of granular phosphinate compound (b) is measured based on the volume-based particle size measured using a laser diffraction / scattering particle size distribution analyzer. Furthermore, the value is measured using a 3% isopropanol aqueous solution as the dispersion medium for phosphinate compound (b). Specifically, using a laser diffraction / scattering particle size distribution analyzer LA-910 (manufactured by Horiba, Ltd.), a blank measurement is performed with a 3% isopropanol aqueous solution as the dispersion medium, and then the sample is added to achieve a specified transmittance (95% to 70%) and measured. The dispersion of the sample in the dispersion medium is performed by irradiating it with ultrasound for 1 minute.

[0056] <Cellulose-based polysaccharides (C) (hereinafter also referred to as component (C))> In this embodiment, the content of cellulose polysaccharides (C) is 0.3 to 10% by mass, preferably 0.5 to 8% by mass, and more preferably 1 to 6% by mass, based on 100% by mass of the flame-retardant styrene resin composition. By setting the content of cellulose polysaccharides (C) to 0.3% by mass or more, low smoke emission flame retardancy and rigidity can be improved. On the other hand, if the content is too high, the moldability will be significantly reduced due to a decrease in fluidity. The content of cellulose polysaccharides in the composition can be determined by dissolving the composition in a solvent that dissolves styrene resin, removing the undissolved material, and measuring the mass of the dried material at 120°C for 4 hours.

[0057] The shape of the cellulosic polysaccharide (C) in this embodiment is not particularly limited and can be spherical, irregular, powdery, flaky, fibrous, rod-shaped, etc. At least one of the average lengths of the short axis d1 or the long axis d2 of the cellulosic polysaccharide (C) is 0.1 to less than 10 μm, preferably 0.2 to 5 μm, preferably 0.3 to 4 μm, and more preferably 0.5 to 3 μm. If the average lengths of the short axis d1 and the long axis d2 are outside the above range, the rigidity may not be sufficiently exhibited. On the other hand, if the average lengths of the short axis d1 and the long axis d2 are within the above range, the dispersibility of the cellulosic polysaccharide (C) and the phosphinate compound (b) is improved, resulting in a composition with high flame retardancy and rigidity. In the cellulose polysaccharide (C) of this embodiment, the average length of the short axis d1 is less than or equal to the average length of the long axis d2, and it is preferable that the average length of the short axis d1 is less than the average length of the long axis d2. In this invention, the average length of the short axis d1 of the cellulose polysaccharide (C) is determined by measuring the short axis length (minimum length) of 100 cellulose polysaccharide (C) samples using a transmission electron microscope (magnified 5000 times) and taking their arithmetic mean. On the other hand, the average length of the long axis d2 of the cellulose polysaccharide (C) is determined by measuring the long axis length (maximum length) of 100 cellulose polysaccharide (C) samples using a transmission electron microscope (magnified 5000 times) and taking their arithmetic mean. Furthermore, the average length of the short axis d1 of the cellulose polysaccharide (C) is determined by measuring the short axis length (minimum length) of the cellulose polysaccharide (C) and using the same method as for the average length of the long axis d2. The short axis length (minimum length) of cellulosic polysaccharide (C) refers to the length of the thinnest (or shortest) point in the image, while the long axis length (maximum length) refers to the length of the longest point in the image. The stiffness is influenced by the shape of the cellulosic polysaccharide (C); in the case of fibers, it is influenced by the average diameter of the short axis, while for flaky or granular forms, it is influenced by the average diameter of the long axis. In the present invention, the aspect ratio (d1 / d2) of the average length of the short axis d1 and the average length of the long axis d2 of the cellulosic polysaccharide (C) is preferably 1 to 500, more preferably 1.2 to 300, even more preferably 1.5 to 200, and particularly preferably 2 to 100.

[0058] In the present invention, cellulosic polysaccharide (C) refers to a polysaccharide having a β-1,4-glucan structure, and includes cellulose and hemicellulose. Furthermore, as long as the fibers constituting cellulosic polysaccharide (C) are formed from polysaccharides having a β-1,4-glucan structure, the material of cellulosic polysaccharide (C) is not particularly limited. For example, natural cellulose fibers (pulp fibers) such as cellulose fibers derived from higher plants [e.g., wood fibers (wood pulp from conifers, broad-leaved trees, etc.), bamboo fibers, sugarcane fibers, seed hair fibers (cotton linters, bombax cotton, kapok, etc.), gin bark fibers (e.g., hemp, paper mulberry, mitsumata, etc.), leaf fibers (e.g., Manila hemp, New Zealand hemp, etc.)], animal-derived cellulose fibers (sea squirt cellulose, etc.), bacterial-derived cellulose fibers, and chemically synthesized cellulose fibers [cellulose acetate (vinegar)]. Examples include organic acid esters such as cellulose acid, cellulose propionate, cellulose butyrate, cellulose acetate propionate, and cellulose acetate butyrate; inorganic acid esters such as cellulose nitrate, cellulose sulfate, and cellulose phosphate; mixed acid esters such as cellulose acetate nitrate; hydroxyalkylcellulose (e.g., hydroxyethylcellulose (HEC), hydroxypropylcellulose, etc.); carboxyalkylcellulose (carboxymethylcellulose (CMC), carboxyethylcellulose, etc.); alkylcellulose (methylcellulose, ethylcellulose, etc.); and cellulose derivative fibers such as regenerated cellulose (rayon, cellophane, etc.). These cellulose-based polysaccharides (C) may be used individually or in combination of two or more types.

[0059] Among the fibers constituting the above-mentioned cellulosic polysaccharide (C), plant-derived cellulose fibers, such as wood fibers (wood pulp from coniferous trees, hardwoods, bamboo, etc.) or seed hair fibers (cotton linter pulp, etc.), are preferred because they offer high manufacturing efficiency in terms of dispersibility, rigidity, and impact resistance when producing the cellulosic polysaccharide (C), and have appropriate fiber diameter and fiber length. In this embodiment, the lignin content in 100% by mass of cellulose polysaccharide (C) is preferably 20% by mass or less, and more preferably 10% by mass or less. If the lignin content in cellulose polysaccharide (C) is greater than 20% by mass, the odor and discoloration will increase during heat processing, the lignin degradation will become charred black spots, reducing the product value, and problems will occur with white coloring. Furthermore, in this embodiment, it is preferable that hemicellulose be present in an amount of 1% by mass or more relative to 100% by mass of cellulose polysaccharide (C). The inclusion of hemicellulose improves dispersibility with styrene resin (A), thereby improving rigidity and molded appearance. In the present invention, it is preferable to leave these components in a suitable content range rather than completely removing them during the manufacturing process of cellulose polysaccharide (C). Hemicellulose is a polysaccharide composed of sugars such as mannan and xylan, and plays a role in bonding microfibrils by hydrogen bonding with cellulose. In addition, since the solubility parameter (SP value) of hemicellulose is on the more hydrophobic side than that of cellulose, it is considered that hemicellulose has the effect of mitigating the difference in SP values ​​between styrene resin (A) and cellulose polysaccharide (C). Furthermore, by including 1% or more hemicellulose, the bubble diameter becomes smaller, improving compressive strength and heat resistance. The amount of hemicellulose in cellulosic polysaccharides (C) can also be adjusted by refining natural wood raw materials that have a high hemicellulose content. For example, if a raw material with a low hemicellulose content is used, the desired amount can be adjusted by adding hemicellulose obtained by extraction from another raw material. In this case, it is acceptable if the structure of the hemicellulose, such as the ends, is partially different from that of the natural product due to the refining or extraction process. In this embodiment, in order to mitigate the SP value difference between the styrene resin (A) and the cellulosic polysaccharide (C), it is more preferable that hemicellulose be present in an amount of 1% to 25% by mass, even more preferably 2% to 20% by mass, even more preferably 3% to 20% by mass, even more preferably 5% to 19.5% by mass, and particularly preferable that it be present in an amount of 7% to 19.3% by mass, relative to the cellulosic polysaccharide (C) (100% by mass).

[0060] <Dispersant> In this embodiment, a dispersant may be included in the styrene resin composition or styrene resin molded product for the purpose of improving the dispersibility of the flame retardant (B) and the cellulosic polysaccharide (C). The dispersant may be added in an amount of 0.5 to 20 parts by weight per 100 parts by weight of the total of components (A) + (B) + (C). By adding a dispersant, burning and deposits in the extruder can be prevented when compounding the flame retardant (B) and the cellulosic polysaccharide (C) with the styrene resin (A), and the molded appearance can be improved. If the amount of dispersant is less than the predetermined amount, there will be no such effect, and if it is more than the predetermined amount, the heat resistance will decrease. A dispersant with good affinity to the styrene resin (A) will have a greater effect.

[0061] As the dispersant, fatty acid ester compounds, polyethylene glycol compounds, terpene compounds, rosin compounds, fatty acid amides, fatty acids, fatty acid metal salts, etc., can be used. Fatty acid ester compounds, polyethylene glycol compounds, terpene compounds, and rosin compounds are particularly preferred. Aliphatic ester lubricants include methyl laurate, methyl myristate, methyl palmitate, methyl stearate, methyl oleate, methyl erucate, methyl behenate, butyl laurate, butyl stearate, isopropyl myristate, isopropyl palmitate, octyl palmitate, octyl coconut fatty acid ester, octyl stearate, octyl beef tallow fatty acid ester, lauryl laurate, stearyl stearate, behenyl behenate, cetyl myristate, esters of montanic acid and ethylene glycol, esters of montanic acid and glycerin, and monta Examples include esters of montanic acid and butylene glycol, esters of montanic acid and trimethylolethane, esters of montanic acid and trimethylolpropane, esters of montanic acid and pentaerythritol, glycerin monostearate, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan sesquioleate, sorbitan trioleate, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, etc. Two or more of these may be used in combination.

[0062] Terpene resins typically refer to those obtained by copolymerizing terpene monomers alone, or terpene monomers with aromatic monomers, or terpene monomers with phenols in an organic solvent in the presence of a Friedel-Crafts type catalyst, but are not limited to these. They may also be hydrogenated terpene resins obtained by hydrogenating the obtained terpene resin. Examples of terpene resins include α-pinene resins, β-pinene resins, aromatically modified terpene resins, terpene phenol resins, and hydrogenated terpene resins. Examples of terpene monomers include, but are not limited to, C5 hemiterpenes such as isoprene, C10 monoterpenes such as α-pinene, β-pinene, dipentene, d-limonene, myrcene, allocimene, ocimene, α-phellandrene, α-terpinene, γ-terpinene, terpinolene, 1,8-cineole, 1,4-cineole, C10 monoterpenes such as α-terpineol, C15 terpineol such as caryophyllene and longifolene, and C20 diterpenes. Among these compounds, α-pinene, C12, dipentene, and d-limonene are particularly preferred. Examples of aromatic monomers include, but are not limited to, styrene, α-methylstyrene, vinyltoluene, and isopropenyltoluene. Examples of phenols include, but are not limited to, phenol, cresol, xylenol, and bisphenol A.

[0063] Examples of rosin-based resins include gum rosin, wood rosin, tall oil rosin, stabilized rosin obtained by disproportionation or hydrogenation of the rosin, polymerized rosin (typically a dimer), which is a polymer of the rosin, and modified rosin modified with unsaturated acids such as maleic acid, fumaric acid, and (meth)acrylic acid. Examples of rosin derivative resins include esterified products of the rosin-based resins, phenol-modified products, and their esterified products. The rosin-based resins or rosin derivative resins used in the present invention are not limited to these resins.

[0064] Examples of aliphatic amide lubricants include stearamide, oleamide, erucamide, behenamide, ethylenebisstearate, ethylenebisoleamide, ethylenebiserucamide, and ethylenebislauramide. These may be used in combination of two or more types.

[0065] Among fatty acids, saturated fatty acids specifically include lauric acid (dodecanoic acid), isodecanoic acid, tridecylic acid, myristic acid (tetradecanoic acid), pentadecylic acid, palmitic acid (hexadecanoic acid), margaric acid (heptadecanoic acid), stearic acid (octadecanoic acid), isostearic acid, tubercurostearic acid (nonadecanoic acid), 2-hydroxystearic acid, arachidic acid (eicosanoic acid), behenic acid (docosanoic acid), lignoceric acid (tetradocosanoic acid), cerotic acid (hexadocosanoic acid), montanic acid (octadocosanoic acid), melissic acid, etc., with lauric acid, palmitic acid, stearic acid, behenic acid, 12-hydroxystearic acid, and montanic acid being particularly noteworthy.

[0066] Among fatty acids, unsaturated fatty acids include myristoleic acid (tetradecenoic acid), palmitoleic acid (hexadecenoic acid), oleic acid (cis-9-octadecenoic acid), elaidic acid (trans-9-octadecenoic acid), ricinoleic acid (octadecadienoic acid), vaccenic acid (cis-11-octadecenoic acid), linoleic acid (octadecadienoic acid), linolenic acid (9,11,13-octadecatrienoic acid), elestearic acid (9,11,13-octadecatrienoic acid), gadoleic acid (eicosanic acid), erucic acid (docosanoic acid), nervonic acid (tetradocosanoic acid), and others. These may be used in combination of two or more types.

[0067] Examples of fatty acid metal salt lubricants include lithium salts, calcium salts, magnesium salts, zinc salts, and aluminum salts of the fatty acids in the above-mentioned fatty acid lubricants. These may be used in combination of two or more types.

[0068] <Optional addition ingredients> In this embodiment, the flame-retardant styrene resin composition may contain, in addition to components (A) to (C) above, optional additives such as conventionally known additives and processing aids, as necessary, within a range that does not impair the effects of the present invention. Examples of these optional additives include antioxidants, weathering agents, antistatic agents, and fillers.

[0069] Examples of the above-mentioned antioxidants include phenolic compounds, phosphorus compounds, and thioether compounds.

[0070] Examples of the above phenolic antioxidants include 2,6-di-t-butyl-p-cresol, 2,6-diphenyl-4-octadecyloxyphenol, distearyl(3,5-di-t-butyl-4-hydroxybenzyl)phosphonate, 1,6-hexamethylenebis[(3,5-di-t-butyl-4-hydroxyphenyl)propionamide], 4,4'-thiobis(6-t-butyl-m-cresol), 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4, 4'-Butylidenebis(6-t-butyl-m-cresol), 2,2'-Ethylidenebis(4,6-di-t-butylphenol), 2,2'-Ethylidenebis(4-2-butyl-6-t-butylphenol), 1,1,3-Tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-Tris(2,6-dimethyl-3-hydroxy-4-t-butylbenzyl)isocyanurate, 1,3,5-Tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-Tris(3,5-di-t-butyl-4-hydroxybenzyl) Droxybenzyl)-2,4,6-trimethylbenzene, 2-t-butyl-4-methyl-6-(2-acryloyloxy-3-t-butyl-5-methylbenzyl)phenol, stearyl[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate methyl]methane, thiodiethylene glycol bis[(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 1,6-hexamethylenebis[(3,5-di-t-butyl-4-hydroxyphenyl) [Xyphenyl)propionate], bis[3,3-bis(4-hydroxy-3-t-butylphenyl)butyric acid] glycol ester, bis[2--t-butyl-4-methyl-6-(2-hydroxy-3-t-butyl-5-methylbenzyl)phenyl] terephthalate, 1,3,5-tris[(3,5-di-t-butyl-4-hydroxyphenyl)propionyloxyethyl] isocyanurate, 3,9-bis[1,1-dimethyl-2-{(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}ethyl]-2,4,8,Examples include 10-tetraoxaspiro[5,5]undecane and triethylene glycol bis[(3-t-butyl-4-hydroxy-5-methylphenyl)propionate]. These may be used individually or in combination of two or more types.

[0071] Examples of the phosphorus-based antioxidants mentioned above include tris(2,4-di-t-butylphenyl) phosphite, trisnonylphenyl phosphite, tris[2-t-butyl-4-(3-t-butyl-4-hydroxy-5-methylphenylthio)-5-methylphenyl] phosphite, tridecyl phosphite, octyldiphenyl phosphite, di(decyl)monophenyl phosphite, di(tridecyl)pentaerythritol diphosphite, and di(nonylphenyl)pentaerythritol Litol diphosphite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-t-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,4,6-tri-t-butylphenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetra(tridecyl)isopropylidene diphenol diphosphite, tetra(tridecyl)-4,4' -n-Butylidenebis(2--t-butyl-5-methylphenol) diphosphite, hexa(tridecyl)-1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butanetriphosphite, tetrakis(2,4-di-t-butylphenyl)biphenylenediphosphonite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 2,2'-methylenebis(4,6-t-butylphenyl)-2-ethylhexylphosph Examples include phytes, 2,2'-methylenebis(4,6-t-butylphenyl)-octadecyl phosphite, 2,2'-ethylidenebis(4,6-di-t-butylphenyl)fluorophosphite, tris(2-[(2,4,8,10-tetrakis-t-butyldibenzo[d,f][1,3,2]dioxaphosphine-6-yl)oxy]ethyl)amine, and phosphites of 2-ethyl-2-butylpropylene glycol and 2,4,6-tri-t-butylphenol. These may be used individually or in combination of two or more types.

[0072] Examples of the thioether-based antioxidants mentioned above include dialkylthiodipropionates such as dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearyl thiodipropionate, as well as pentaerythritol tetra(β-alkylmercaptopropionate esters). These may be used individually or in combination of two or more types.

[0073] As the weather-resistant agent mentioned above, ultraviolet absorbers, hindered amine light stabilizers, and the like can be used. Examples of the above UV absorbers include 2-hydroxybenzophenones such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 5,5'-methylenebis(2-hydroxy-4-methoxybenzophenone); 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'- 2-(2'-hydroxyphenyl)benzotriazoles such as t-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-dicumylphenyl)benzotriazole, 2,2'-methylenebis(4-t-octyl-6-(benzotriazolyl)phenol), and 2-(2'-hydroxy-3'-t-butyl-5'-carboxyphenyl)benzotriazole; phenyl salicylic acid Benzoates such as benzoates, resorcinol monobenzoate, 2,4-di-t-butylphenyl-3,5-di-t-butyl-4-hydroxybenzoate, 2,4-di-t-amylphenyl-3,5-di-t-butyl-4-hydroxybenzoate, hexadecyl-3,5-di-t-butyl-4-hydroxybenzoate; substituted oxanilides such as 2-ethyl-2'-ethoxyoxanilide and 2-ethoxy-4'-dodecyloxanilide; ethyl-α-cyano-β,β-diphenylacrylate, methyl Examples include cyanoacrylates such as 2-2-cyano-3-methyl-3-(p-methoxyphenyl)acrylate; and triaryltriazines such as 2-(2-hydroxy-4-octoxyphenyl)-4,6-bis(2,4-di-t-butylphenyl)-s-triazine, 2-(2-hydroxy-4-methoxyphenyl)-4,6-diphenyl-s-triazine, and 2-(2-hydroxy-4-propoxy-5-methylphenyl)-4,6-bis(2,4-di-t-butylphenyl)-s-triazine. These may be used individually or in combination of two or more types.

[0074] Examples of the above hindered amine-based light stabilizers include 2,2,6,6-tetramethyl-4-piperidyl stearate, 1,2,2,6,6-pentamethyl-4-piperidyl stearate, 2,2,6,6-tetramethyl-4-piperidyl benzoate, bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1,2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, and tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1 ,2,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, bis(2,2,6,6-tetramethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,4,4-pentamethyl-4-piperidyl)-2-butyl-2-(3,5-di-t-butyl-4-butyl) Droxybenzyl)malonate, 1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-piperidinol / diethyl succinate polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-morpholino-s-triazine polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-t-octylamino-s-triazine polycondensate, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl [2,4-bi-4-piperidyl)amino)-s-triazine-6-yl]-1,5,8,12-tetraazadodecane, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino)-s-triazine-6-yl]-1,5,8-12-tetraazadodecane, 1,6,11-tris[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4-piperidyl)amino)-s-triazine-6-yl]aminoundecane, 1,6,11-tris[2,4-bis(N-butyl-N-(1,2,Examples of hindered amine compounds include 2,6,6-pentamethyl-4-piperidyl)amino)-s-triazine-6-yl]aminoundecane. These may be used individually or in combination of two or more types.

[0075] As the above-mentioned antistatic agent, cationic, anionic, nonionic, amphoteric, fatty acid partial esters such as glycerol fatty acid monoesters can be used. Specifically, alkyltrimethylammonium salts, dialkyldimethylammonium salts, benzalkonium salts, N,N-bis(2-hydroxyethyl)-N-(3-dodecyloxy-2-hydroxypropyl)methylammonium mesosulfate, (3-laurylamidopropyl)trimethylammonium methylsulfate, stearamidopropyldimethyl-2-hydroxyethylammonium nitrate, stearamidopropyldimethyl-2-hydroxyethylammonium phosphate, cationic polymers, alkyl sulfonates, alkylbenzene sulfonates, alkyldiphenyl ether disulfonate sodium, alkyl nitrate esters, phosphorus Examples include alkyl acid ester salts, alkyl phosphate amine salts, monoglyceride stearate, pentaerythritol fatty acid esters, sorbitan monopalmitate, sorbitan monostearate, diglycerin fatty acid esters, alkyldiethanolamine, alkyldiethanolamine fatty acid monoesters, alkyldiethanolamide, polyoxyethylene dodecyl ether, polyoxyethylene alkylphenyl ether, polyethylene glycol monolaurate, polyoxyethylene alkylamine, polyoxyethylene alkylamide, polyether block copolymer, cetyl betaine, and hydroxyethylimidazoline sulfate. These may be used individually or in combination of two or more types.

[0076] Examples of fillers that can be used include talc, calcium carbonate, barium sulfate, carbon fiber, mica, wollastonite, and whiskers.

[0077] In this embodiment, the flame-retardant styrene resin composition may contain, in addition to the above-mentioned optional additives, optional additives such as blocking inhibitors, colorants, blooming inhibitors, surface treatment agents, antibacterial agents, and eye discharge inhibitors (eye discharge inhibitors such as silicone oil described in Japanese Patent Application Publication No. 2009-120717, monoamide compounds of higher aliphatic carboxylic acids, and monoester compounds obtained by reacting higher aliphatic carboxylic acids with monovalent to trivalent alcohol compounds). In this embodiment, the total content of the optional additives may be 0.05 to 5% by mass in the flame-retardant styrene resin composition.

[0078] The flame-retardant styrene resin composition of this embodiment may consist substantially only of component (A), component (B), and component (C). Alternatively, the flame-retardant styrene resin composition may consist substantially only of component (A), component (B), component (C), a dispersant, and an optional additive. "Substantially consisting only of components (A), (B), and (C)" means that components (A), (B), and (C) account for 80 to 100% (preferably 88 to 100% by mass) of the total amount (100% by mass) of the flame-retardant styrene resin composition. "Substantially consisting only of component (A), component (B), component (C), a dispersant, and optional additives" means that 95 to 100% (preferably 98 to 100% by mass) of the total amount (100% by mass) of the flame-retardant styrene resin composition is comprised of component (A), component (B), component (C), a dispersant, and optional additives. Furthermore, the flame-retardant styrene resin composition of this embodiment may contain unavoidable impurities in addition to components (A), (B), (C), a dispersant, and optional additives, as long as the effects of the present invention are not impaired.

[0079] The flame-retardant styrene resin composition of this embodiment is formed from a styrene resin composition containing predetermined amounts of a styrene resin (A), a phosphinate compound (b), a cellulose polysaccharide (C) having an average length of at least one of its short axis d1 or long axis d2 of 10 to 80 μm, and a dispersant and / or optional additives, which are added as needed. The materials and properties of the styrene resin (A), phosphinate compound (b), cellulose polysaccharide (C), and the dispersant and / or optional additives added to the styrene resin composition are as described above. Furthermore, the amounts of these components (A), (B), (C), dispersant and optional additives can be appropriately adjusted so that their content in the flame-retardant styrene resin composition falls within the above range.

[0080] <Method for producing flame-retardant styrene-based resin composition> The flame-retardant styrene resin composition of this embodiment can be manufactured by melt-kneading each component in any manner. For example, methods include using a high-speed agitator such as a Henschel mixer, a batch-type kneader such as a Banbury mixer, a single-screw or twin-screw continuous kneader, a roll mixer, etc., either individually or in combination. The heating temperature during kneading is usually selected in the range of 180 to 260°C.

[0081] [Physical properties of flame-retardant styrene-based resin compositions] <Flame-retardant> The flame retardancy of the flame-retardant styrene resin composition of this embodiment is preferably within the standards in the UL94 vertical combustion test (UL94-V test), i.e., a flame retardancy class of V-0 to V-2. Furthermore, it is preferable that no black smoke is generated during combustion. In this disclosure, flame retardancy and black smoke can be evaluated by the methods described in the [Examples] section below.

[0082] <Flexural modulus> The flexural modulus of the molded article obtained from the flame-retardant styrene resin composition of this embodiment is preferably 2800 MPa or higher, and more preferably 3000 MPa or higher. In this disclosure, the flexural modulus is a value measured in accordance with ISO 178.

[0083] <Yellow Index> The yellow index of the flame-retardant styrene resin composition of this embodiment is preferably 20 or less, and more preferably 15 or less. If it is greater than 20, coloring may become difficult.

[0084] [Molded products] The flame-retardant styrene resin composition of this embodiment can be used to produce molded articles by the above-described melt-kneading molding machine, or by using the resulting flame-retardant styrene resin composition pellets as a raw material, through injection molding, injection compression molding, extrusion molding, blow molding, press molding, vacuum molding, foam molding, and the like.

[0085] Molded articles containing the flame-retardant styrene resin composition of this embodiment are preferably suitable for use in injection molded articles (including injection compression), office automation equipment such as photocopiers, fax machines, televisions, radios, tape recorders, video decks, personal computers, printers, telephones, information terminals, refrigerators, and microwave ovens, as well as housings and various parts for home electrical appliances and electrical and electronic equipment, foamed insulation materials, insulating films, and the like. [Examples]

[0086] The embodiments of the present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited in any way by these embodiments. <Measurement and Evaluation Methods> The physical properties of the resin compositions obtained in each example and comparative example were measured and evaluated based on the following methods. (1) Evaluation of flame retardancy (i) Evaluation of combustion grade and burn time Using test specimen (b) (size: 127 mm × 12.7 mm, thickness: 1.5 mm) prepared by the method described below, flame retardancy was evaluated in accordance with the UL94 vertical combustion test (UL94-V test) using a 50W test flame. The degree of combustion was evaluated by applying a gas burner flame to the above test specimen (b). The flame retardancy rating indicates the flame retardancy class classified by the UL94-V test. Five tests were conducted on each test specimen for evaluation. The general classification method is as follows: V-0: Total burning time of 5 sticks is 50 seconds or less, maximum burning time is 10 seconds or less, no drip cotton ignition. V-1: Total burning time of 5 sticks is 250 seconds or less, maximum burning time is 30 seconds or less, no drip cotton ignition. V-2: Total burning time of 5 sticks is 250 seconds or less, maximum burning time is 30 seconds or less, with drip cotton ignition. Not V: Not conforming to UL94 standards Furthermore, the generation of black smoke during combustion was judged visually. If black smoke was generated during combustion, it was marked with ×; if a small amount was generated, it was marked with △; and if almost no black smoke was generated, it was marked with ○.

[0087] (2) Flexural modulus The flexural modulus was measured using test specimen (a) prepared according to the method described below, in accordance with ISO 178.

[0088] (3) Yellow Index For the test specimens (a) prepared using the method described below, the yellow index of the resin composition was measured using a COH300A (product name) color difference turbidity meter manufactured by Nippon Denshoku Co., Ltd., in accordance with JIS K7105. A value of 5 or less was considered acceptable, taking into account the purpose of color matching.

[0089] (4) Content of styrene monomer units, methacrylic acid monomer units, and methyl methacrylate monomer units in styrene resin (a) Proton nuclear magnetic resonance ( 1 The resin composition was quantified from the integral ratio of the spectra measured using a 1H-NMR (H-NMR) detector. Sample preparation: 30 mg of resin pellets were dissolved in 0.75 mL of d6-DMSO by heating at 60°C for 4-6 hours. ·Measuring equipment: JNM ECA-500 manufactured by JEOL Ltd. • Measurement conditions: Measurement temperature 25°C, observed nucleus 1 H, cumulative count 64 times, repetition time 11 seconds.

[0090] (Attribution of the spectrum) Regarding the assignment of the spectra measured in dimethyl sulfoxide deuterated solvent, the peaks at 0.5–1.5 ppm are derived from hydrogen atoms of the α-methyl groups of methacrylic acid, methyl methacrylate, and six-membered cyclic acid anhydrides; the peaks at 1.6–2.1 ppm are derived from hydrogen atoms of the methylene groups of the polymer main chain; the peak at 3.5 ppm is derived from hydrogen atoms of the carboxylic acid ester (-COOCH3) of methyl methacrylate; and the peak at 12.4 ppm is derived from hydrogen atoms of the carboxylic acid of methacrylic acid. In addition, the peaks at 6.5–7.5 ppm are derived from hydrogen atoms of the aromatic ring of styrene. Note that in the resins of this example and comparative example, the content of six-membered cyclic acid anhydrides is low, so quantification is usually difficult using this measurement method.

[0091] (5) Measurement of the average length of cellulosic polysaccharides (C) Ultrathin sections with a thickness of 75 nm were prepared from pellets obtained from the kneaded material, and photographs were taken at a magnification of 50,000x using an electron microscope. The photographs were then scanned at a resolution of 200 dpi, and the minimum and maximum lengths of 100 cellulosic polysaccharides (C) were measured using particle analysis software on the image analysis device IP-1000 (manufactured by Asahi Kasei Corporation). The arithmetic mean of these lengths was taken as the average length d1 along the short axis and the average length d2 along the long axis. Similarly, individual cellulosic polysaccharides (C) were also photographed at a magnification of 50,000x using an electron microscope, and the arithmetic mean of these lengths was taken as the average length d1 along the short axis and the average length d2 along the long axis.

[0092] (6) Determination of lignin content The quantitative analysis of lignin in cellulosic polysaccharides (C) was performed using the TGA method described in the Transactions of the Japan Society of Waste Management and Resource Recycling, Vol. 22, No. 5, P293, 2011. A Shimadzu DTG-60 thermogravimetric analyzer was used, and the temperature was raised from room temperature to 900°C at a heating rate of 10°C / min under an air atmosphere. The sample to be analyzed was dried at 70°C for 2 hours, and 3-5 mg was accurately weighed; the weight change due to thermal decomposition was measured. A circular platinum dish with an inner diameter of 5 mm and a height of 2 mm was used as the sample container, and all experiments were conducted under consistent conditions.

[0093] (7) Measurement of hemicellulose content The quantitative analysis of hemicellulose in cellulosic polysaccharides (C) is as follows: The dispersion medium was removed from a dispersion of cellulose polysaccharide (C), or from a redispersion of cellulose polysaccharide (C) obtained by dissolving and removing the resin component from a styrene resin composition. The cellulose residue was recovered, and the mass of the dried sample obtained by drying at 105°C was measured by the following method. The dried cellulose residue was pulverized to obtain a pulverized sample, which was extracted in a Soxhlet extractor with an alcohol (ethanol) / benzene mixed solvent for 6 hours. Then, extraction was performed for another 4 hours with the same alcohol (ethanol) / benzene mixed solvent to obtain a defatted sample. 2.5 g of this defatted sample was mixed with 150 mL of distilled water, 1.0 g of sodium chlorite, and 0.2 mL of acetic acid. The sample was heated at 70-80°C for 1 hour, and then repeated 3-4 times, adding another 1.0 g of sodium chlorite and 0.2 mL of acetic acid and heating at 70-80°C for 1 hour, until the sample became white and decolorized. The resulting sample was filtered, washed with water and acetone, and dried at 105°C to obtain a holocellulose fraction (total amount of α-cellulose and hemicellulose). The mass of this holocellulose fraction was measured. Next, 25 mL of 17.5% by mass sodium hydroxide aqueous solution was added to 1.0 g of the holocellulose fraction, and after 3 minutes, it was gently crushed with a glass rod until it swelled. After that, it was allowed to stand at 20°C, and 30 minutes after adding the sodium hydroxide aqueous solution, 25 mL of distilled water was added, and it was stirred for exactly 1 minute, then allowed to stand at 20°C for 5 minutes, and filtered through a glass filter and washed until the filtrate was neutral. Furthermore, 40 mL of 10% by mass acetic acid was filtered by suction, and then 1 L of boiling water was filtered by suction to wash the sample, which was then dried at 105°C until the mass became constant to obtain the α-cellulose fraction. The mass of this α-cellulose fraction was measured. From the masses of the holocellulose fraction and α-cellulose fraction obtained as described above, the hemicellulose content was determined by the following formula. Holocellulose (%) = Holocellulose fraction (g) / Sample (anhydrous base) (g) × 100 α-cellulose (%) = α-cellulose fraction (g) / sample (anhydrous base) (g) × 100 Hemicellulose (%) = Holocellulose (%) - (α-cellulose (%))

[0094] (8) Method for measuring the average particle size of phosphinate compounds (b) The average particle size of granular phosphinate compound (b) is measured based on the volume-based particle size measured using a laser diffraction / scattering particle size distribution analyzer. The value is measured using a 3% isopropanol aqueous solution as the dispersion medium for phosphinate compound (b). Specifically, a LA-910 laser diffraction / scattering particle size distribution analyzer (manufactured by Horiba, Ltd.) was used to perform a blank measurement with a 3% isopropanol aqueous solution as the dispersion medium, and then the sample was added to achieve a specified transmittance (95% to 70%) and measured. The dispersion of the sample in the dispersion medium was performed by irradiating it with ultrasound for 1 minute.

[0095] The materials used in the examples and comparative examples are as follows. [Styrene resin (A)] [GPPS-1] • Polystyrene with an MFR of 7.8 (GPPS, manufactured by PS Japan, HF77) was used. [HIPS-1] • A rubber-modified polystyrene resin (HIPS, manufactured by PS Japan, HT478) with an MFR of 3.0 was used.

[0096] [Copolymer resin-1] A polymerization raw material composition liquid consisting of 70.0 parts by mass of styrene (ST), 15.0 parts by mass of butyl methacrylate (BA), 15.0 parts by mass of ethylbenzene, and 0.025 parts by mass of 1,1-bis(t-butylperoxy)cyclohexane was continuously supplied at a rate of 1.1 liters / hour to a 4-liter fully mixed reactor, then to a polymerization apparatus consisting of a 2-liter laminar flow reactor, and finally to a defoliation apparatus connected to a single-screw extruder for removing volatile components such as unreacted monomers and polymerization solvents, thereby preparing copolymer resin-1, a styrene-based copolymer resin. The polymerization reaction conditions in the polymerization process were set to a polymerization temperature of 122°C for the fully mixed reactor and 120-142°C for the laminar flow reactor. The defolatable unreacted gas was condensed in a condenser through a refrigerant at -5°C and recovered as unreacted liquid. The polymer content in the final polymerization solution was measured using the formula [(mass of sample after drying / mass of sample before drying) × 100%] after drying the polymerization solution at 215°C under reduced pressure of 2.5 kPa for 30 minutes, and was 65.6% by mass, with an MFR of 4.6.

[0097] [Blend - 1] The above HIPS-1 was compounded with 5% by mass of styrene-maleic anhydride copolymer (XIBOND250, manufactured by POLYSCOPE), and the MFR was 3.2.

[0098] [Phosphinate compounds (b)] • Aluminum phosphinate (also referred to as DEP-A in Tables 1 and 2) "Exolit OP1230 manufactured by Clariant Japan" Average particle size 20 μm • Aluminum phosphinate (also referred to as DEP-B in Tables 1 and 2) "Exolit OP930 manufactured by Clariant Japan" Average particle size: 3 μm • Aluminum phosphinate (also referred to as DEP-C in Tables 1 and 2) was manufactured according to the method described in Japanese Patent Publication No. 08-73720. Average particle size: 0.8 μm • Phosphate ester: Resorcinol bis-dixylenyl phosphate [Manufactured by Daihachi Chemical Industry Co., Ltd., PX-200, melting point 92℃]

[0099] [Cellulose polysaccharides (C)] • CNF-1: Cellulose nanofiber (manufactured by Chuetsu Pulp & Paper Co., Ltd., CNF-10, d1: 35 nm, d2: approximately 1 μm, lignin content 0%, hemicellulose content 15% by mass) • CNF-2: Cellulose nanofiber (manufactured by Daicel Finechem Co., Ltd., KY-100G, d1: 100nm, d2: approx. 8μm, lignin content 0%, hemicellulose content 0.3% by mass) • Cellulose fiber (Celite, SW-10, d1: 20 μm, d2: 700 μm, lignin content 0.5%, hemicellulose content 11% by mass) • Hemicellulose (manufactured by Wako Pure Chemical Industries, Xylan)

[0100] [Examples 1-10] To 100 parts by mass of a total amount of styrene resin (A) and cellulosic polysaccharide (B) in the composition ratios shown in Table 1 below, 0.2 parts by mass each of Irganox 1076 and Irgafos 168 were added and pre-mixed. The resulting pre-mixture was mixed together and melt-extruded using a twin-screw extruder (Toshiba Machine Co., Ltd., TEM-26SS) at a temperature of 180°C to 220°C to obtain pellets of a flame-retardant styrene resin composition as a kneaded product. At this time, the screw rotation speed was 250 rpm and the discharge rate was 10 kg / hr. The pelletized flame-retardant styrene resin composition obtained in this manner was molded using an injection molding machine manufactured by Japan Steel Works, Ltd. equipped with an ISO 527-2 multipurpose test specimen type 1A, with a cylinder temperature of 220°C, a mold temperature of 50°C, an injection pressure (gauge pressure of 40-60 MPa), an injection speed (panel setting) of 50%, and an injection time / cooling time of 5 sec / 20 sec to produce test specimen (a), and its various physical properties were measured. In addition, test specimen (b) was prepared using a double-gate flat plate mold with dimensions of 127 mm × 12.7 mm × thickness of 0.8 mm under the same conditions as test specimen (a), and its flame retardancy was measured. The experimental results of Examples 1 to 10 are shown in Table 1.

[0101] [Comparative Examples 1-12] Comparative Examples 1 to 12 were obtained in the same manner as the Examples, except that the composition was changed as shown in Table 2. The results of the measurement and evaluation of each physical property are shown in Table 2.

[0102] [Table 1]

[0103] [Table 2]

[0104] As shown in Table 1 above, the flame-retardant styrene resin compositions obtained in Examples 1 to 10 were compositions with excellent low-smoke flame retardancy, rigidity, and color. In particular, it was confirmed that low-smoke flame retardancy was enhanced when the composition contained an unsaturated carboxylic acid monomer and the amount of hemicellulose in the cellulosic polysaccharide (C) was 1% by mass or more.

[0105] As shown in Table 2, low smoke emission, flame retardancy, and rigidity cannot be obtained with phosphinate compound (b) alone. Furthermore, low smoke emission, flame retardancy, and rigidity cannot be obtained with cellulose polysaccharide (C) alone, and discoloration due to cellulose is also significant. Moreover, if the size of cellulose polysaccharide (C) is large, low smoke emission, flame retardancy, and rigidity cannot be obtained. Also, if phosphinate compound (b) is changed to a phosphate ester, low smoke emission and rigidity cannot be obtained. Furthermore, if the amount of phosphinate compound (b) or cellulose polysaccharide (C) exceeds the specified amount, the fluidity is poor and molding cannot be performed.

[0106] Furthermore, experimental results from the examples and comparative examples show that when the average length of the short axis d1 or long axis d2 of the cellulose polysaccharide (C) (e.g., cellulose nanofiber) is smaller than the average particle size of the phosphinate compound (b), the cellulose polysaccharide (C) (e.g., cellulose nanofiber) adheres to (or clings to) the phosphinate compound (b), thereby improving the dispersibility of each component in the flame-retardant resin composition (especially the cellulose polysaccharide (C) or phosphinate compound (b)), resulting in improved low smoke emission, flame retardancy, rigidity, and color tone. On the other hand, in the case of materials with a diameter larger than the average particle size of phosphinate compound (b), such as cellulose fibers, the flame retardant components such as phosphinate compound (b) adhere to (or cling to) the cellulose fibers, and it is thought that the microstructure of the two materials changes when compared to the example using cellulosic polysaccharide (C). [Industrial applicability]

[0107] The flame-retardant styrene resin composition of the present invention can be suitably used in building materials, electronic and electrical components, automobiles, food container foams, and the like.

Claims

1. 60 to 96.7% by mass of a styrene-based resin (A), The following general formula (i): 【Chemistry 1】 [In the above formula (i), R i1 and R i2 are each independently unsubstituted or one or more hydrogen atoms are substituted by R i3 a linear or branched alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an aralkyl group having 6 to 14 carbon atoms, which may be substituted by The substituent R i3 is represented by the following formula (ii): 【Chemistry 2】 "In the above formula (ii), R ii1 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, and * represents a bond to another atom. M i is at least one selected from the group consisting of calcium ions, magnesium ions, aluminum ions, zinc ions, bismuth ions, manganese ions, sodium ions, potassium ions, and protonated nitrogen bases, and p + is M i represents the ionic valence of the compound, and is a positive integer of 1 to 3; i1 is a positive integer from 1 to 3, and n - represents a negative integer of −1, −2, or −3, r represents a positive integer of 1 to 3, and |p + ×r|=|n - ×m i1 3 to 30 mass % of a flame retardant (B) containing a phosphinate compound (b) represented by the formula: | short axis d 1 Or the major axis d 2 and 0.3 to 10 mass % of a cellulose-based polysaccharide (C) having an average length of at least one of the above from 0.1 to less than 10 μm.

2. 2. The flame-retardant styrene-based resin composition according to claim 1, wherein the phosphinic acid compound (b) is at least one or more compounds selected from the group consisting of phosphinic acid salts represented by the following general formula (1) and diphosphinic acid salts represented by the following general formula (2): 【Transformation 3】 [In the above formula (1), R 11 and R 12 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, M 1 is at least one selected from the group consisting of calcium ions, magnesium ions, aluminum ions, zinc ions, bismuth ions, manganese ions, sodium ions, potassium ions, and protonated nitrogen bases, and a + is M 1 represents an ionic valence of 1 to 3, and is a positive integer of 1 to 3; 1 is a positive integer between 1 and 3, and a=m 1 It is.] 【Chemistry 4】 [In the formula, R 21 and R 22 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, and L 23 is a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 6 to 14 carbon atoms, or an arylalkylene group having 6 to 14 carbon atoms; M 2 is at least one selected from the group consisting of calcium ions, magnesium ions, aluminum ions, zinc ions, bismuth ions, manganese ions, sodium ions, potassium ions, and protonated nitrogen bases; b + is M 2 represents the ionic valence of the compound, and is a positive integer of 1 to 3; 2 is a positive integer from 1 to 3, q ​​is a positive integer of 1 or 2, and b×q=2m 2 It is.]

3. 3. The flame-retardant styrene-based resin composition according to claim 1, wherein the styrene-based resin (A) contains a styrene-based monomer unit and an unsaturated carboxylic acid-based monomer unit.

4. The flame-retardant styrene-based resin composition according to claim 1 or 2, wherein the cellulose (B) is a cellulose containing 20 mass% or less of lignin.

5. The flame-retardant styrene-based resin composition according to any one of claims 1 to 4, characterized in that the cellulose-based polysaccharide (B) has a hemicellulose content of 1% or more.

6. A molded article comprising the flame-retardant styrene-based resin composition according to any one of claims 1 to 5.